Effects of Suboptimization on Urban Government Decision Making: Dicussion - Due, John F. (Journal of Finance, 1971)
John F. Due, Effects of Suboptimization on Urban Government Decision Making: Dicussion, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 579-580